2022
DOI: 10.1039/d2tb00184e
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic multifunctional nanozymes enhanced radiosensitization for breast cancer via an X-ray triggered cascade reaction

Abstract: Radiotherapy was widely applied for breast cancer treatment in clinical, while how to improve the radiation sensitivity of tumor and protect normal tissues form radiation damage had drawn considerable attention....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Preparation of BSA-Incubated Cerium Oxide Nanoparticles (CeO2@BSA Nanoparticles): According to previous literature reports, [24,54] 0.25 mL of Ce(NO 3 ) 3 •6H 2 O (0.1 m, Aladdin) aqueous solution was first mixed with 4.5 mL BSA solution (25 mg mL −1 , Aladdin), and then stirred vigorously at 80 °C for 15 min. Subsequently, the above mixed solution was rapidly added to 0.3 mL of KOH solution (1 m, Aladdin) and the reaction was stirred for 2 h. The obtained product was then dialyzed in ultrapure water for 24 h using dialysis bags (Thermo Scientific, 10 kD).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preparation of BSA-Incubated Cerium Oxide Nanoparticles (CeO2@BSA Nanoparticles): According to previous literature reports, [24,54] 0.25 mL of Ce(NO 3 ) 3 •6H 2 O (0.1 m, Aladdin) aqueous solution was first mixed with 4.5 mL BSA solution (25 mg mL −1 , Aladdin), and then stirred vigorously at 80 °C for 15 min. Subsequently, the above mixed solution was rapidly added to 0.3 mL of KOH solution (1 m, Aladdin) and the reaction was stirred for 2 h. The obtained product was then dialyzed in ultrapure water for 24 h using dialysis bags (Thermo Scientific, 10 kD).…”
Section: Methodsmentioning
confidence: 99%
“…The average particle size of CeNPs measured by dynamic light scattering (DLS) was about 4.97 ± 1.39 nm (Figure 2b). In order to assess the stability of CeNPs, the diameter of nanoparticles after storage at 4 °C for different times (12,24,48,72, and 96 h) was detected and no significant change was found (Figure S1a, Supporting Information). According to the result of Fourier transform infrared (FT-IR) spectroscopy, CeNPs and BSA had common characteristic peaks (1650 and 3300 cm −1 ), confirming the existence of BSA in CeNPs (Figure 2c).…”
Section: Fabrication and Characterization Of Cenpsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the recent statistics of the International Agency for Research on Cancer, breast cancer has become the most diagnosed cancer in both sexes [87]. Much attention has been paid to develop novel materials for breast cancer treatment [88][89][90][91].…”
Section: Breast Cancer Treatmentmentioning
confidence: 99%
“…Moreover, in clinical practice, radiotherapy inevitably causes irreversible damage to normal tissues and cells [9][10][11]. Therefore, the development of radiotherapy sensitizers can greatly overcome the shortcomings of conventional radiotherapy and reduce the toxic side effects caused by conventional radiotherapy [12][13][14]. Currently, it has been found that many materials have the ability to enhance the sensitivity of tumor cells to X-rays, such as the small molecule paclitaxel [15][16][17] and metal complexes [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%